The Rise and Struggle of Presidents during the Coronavirus Emergency: National and Sub-national Evidence in Italy and Spain - Fittipaldi, Raffaella (PARTECIPAZIONE E CONFLITTO, 2021)
This article aims to explore the expansion of power of monocratic figures during the Covid-19 crisis. In particular, it compares the Italian and Spanish cases, at both national and sub-national levels, during the pandemic. First, we explore the dynamics of personalization through an empirical analysis of emergency decrees at the state level. Second, we examine personalization as evidence of centre-periphery conflict by taking into consideration regional rules (decrees, orders, regulations, resolutions) and their relation to the state level. The comparison shows a similar path of institutional personalization of politics in Italy and Spain, with both countries displaying the features of an unstable regional framework.